2019
DOI: 10.1177/0305735619864634
|View full text |Cite
|
Sign up to set email alerts
|

Choosing to study music in high school: Teacher support, psychological needs satisfaction, and elective music intentions

Abstract: High school students do not value music education highly, nor do they see it as a useful part of their academic pathways. When music becomes an elective subject, low enrolment in elective classes is seen as a challenge for music educators. This study aimed to further investigate this issue by examining the motivational climate of the music classroom, including the perceptions of the music teacher, in the development of student motivation for music. It also examined how these motivational factors influenced stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 60 publications
2
40
1
1
Order By: Relevance
“…Freer & Evans, 2018; Legutki, 2010), socioeconomic status (Elpus, 2014; Elpus & Abril, 2011; Kinney, 2010), and positive attitude toward music (Lucas, 2011; Moder, 2018). Additionally, researchers have focused on social factors (e.g., parents, teachers, peers) that are likely to have a vital impact on students’ motivation for continued music involvement (Dagaz, 2012; E. Freer & Evans, 2019; Hewitt & Allan, 2013; Ng & Hartwig, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Freer & Evans, 2018; Legutki, 2010), socioeconomic status (Elpus, 2014; Elpus & Abril, 2011; Kinney, 2010), and positive attitude toward music (Lucas, 2011; Moder, 2018). Additionally, researchers have focused on social factors (e.g., parents, teachers, peers) that are likely to have a vital impact on students’ motivation for continued music involvement (Dagaz, 2012; E. Freer & Evans, 2019; Hewitt & Allan, 2013; Ng & Hartwig, 2011).…”
mentioning
confidence: 99%
“…Freer & Evans, 2019; Hewitt & Allan, 2013; Ng & Hartwig, 2011). In classroom settings, the teacher represents a central leader who interacts with students regularly and is an important source of support (E. Freer & Evans, 2019; Graves, 2019).…”
mentioning
confidence: 99%
“…First, secondary music teachers can connect with local elementary school music programs to support positive elementary music experiences and subsequent enrollment in secondary programs (Freer & Evans, 2018; Miksza, 2013b; Ruybalid, 2016). When general music students in elementary and middle school leave their music class with stronger beliefs in their music abilities, they are more likely to enroll in secondary music classes (Freer & Evans, 2018, 2019). Second, at the secondary level, music educators might design music experiences for students who do not participate in school music classes to help them better understand their music abilities and their potential for developing their musicianship (Dweck, 2006; Legette, 1998).…”
Section: Intrapersonal Factors Related To Secondary Music Participationmentioning
confidence: 99%
“…This may influence the results because of developmental changes that occur during this time period (Wigfield, Eccles, Schiefele, Roeser, & Davis-Kean, 2006). However, other research in the area of music and elective choice (Freer & Evans, 2019) tested this using multiple group analysis and found that there were no differences between levels of motivation and influence of motivation on elective choice between Year 7 and Year 8. Future studies could investigate students' elective choices when they are entering their final years of school.…”
Section: Limitations and Implications For Future Studiesmentioning
confidence: 99%